A memória, o grupo e o ator: ligações e tensões acerca da formação da identidade do militante estudantil de 1968 - Augustinho, Aline Michele Nascimento [UNESP] (2015)
The objective of this study was to draw an analysis to identify the formation of the concept of identity of the student activist agent in 1968 from the three planes relationship: the memory, the group and the actor, which are inserted and influence cyclical and each other to same time offer a dynamic table between society, the collective memory and the symbolic creation of the group. We tried to thus self identification of former militant through the social construction of the movement and the group symbology memory. When considering the past, the construction of identity takes place in relation to the group and its subjective perception. The bond with the group would, it is estimated, rebuilt every reworking process your personal memory of their participation in the ME. The memory as an analytical tool appears in the following analyzes: in the literary productions of 1968; in surveys and investigations of repression, expressed by Dops files on the action of the students served the ME and the subsequent symbolic construction of the group as a threat to internal order, and finally, development of memory boards on the particular path. It shows, so, with the balance of subjective construction that the individual makes of himself when it binds to the historical memory through its group, while the literature and the files are in the opposite direction: objectively observe an individual's why he was part of that group. In remembrance of work, memory, subjective or built by literature always travel this path in both directions, although in the same direction. She founded the individual by the group and the group by the individual in their speech